VRIO Analysis as a Basic Strategy for Obtaining Construction Tenders in Construction Service Companies - Wulandari, Cresentiana Cythia; Agustini, Maria Y. D. Hayu (Soegijapranata Catholic University, 2024)
This research is related to the condition of PT XY which has not been able to reach the target to get a construction tender. The aim of this research is to determine the right strategy in obtaining construction tenders based on the results of an analysis of internal conditions using VRIO analysis. The object of research is the strategy to obtain a construction tender for PT XY, a private construction service company with a